Extensive Anti-CoA Immunostaining in Alzheimer’s Disease and Covalent Modification of Tau by a Key Cellular Metabolite Coenzyme A - Lashley, Tammaryn; Tossounian, Maria-Armineh; Costello Heaven, Neve; Wallworth, Samantha; Peak-Chew, Sew; Bradshaw, Aaron; Cooper, J. Mark; de Silva, Rohan; Srai, Surjit Kaila; Malanchuk, Oksana; Filonenko, Valeriy; Koopman, Margreet B.; et al. (Frontiers in Cellular Neuroscience, 2021)
Alzheimer’s disease (AD) is a neurodegenerative disorder, accounting for at least two-thirds of dementia cases. A combination of genetic, epigenetic and environmental triggers is widely accepted to be responsible for the onset and development of AD. Accumulating evidence shows that oxidative stress and dysregulation of energy metabolism play an important role in AD pathogenesis, leading to neuronal dysfunction and death. Redox-induced protein modifications have been reported in the brain of AD patients, indicating excessive oxidative damage. Coenzyme A (CoA) is essential for diverse metabolic pathways, regulation of gene expression and biosynthesis of neurotransmitters. Dysregulation of CoA biosynthesis in animal models and inborn mutations in human genes involved in the CoA biosynthetic pathway have been associated with neurodegeneration. Recent studies have uncovered the antioxidant function of CoA, involving covalent protein modification by this cofactor (CoAlation) in cellular response to oxidative or metabolic stress. Protein CoAlation has been shown to both modulate the activity of modified proteins and protect cysteine residues from irreversible overoxidation. In this study, immunohistochemistry analysis with highly specific anti-CoA monoclonal antibody was used to reveal protein CoAlation across numerous neurodegenerative diseases, which appeared particularly frequent in AD. Furthermore, protein CoAlation consistently co-localised with tau-positive neurofibrillary tangles, underpinning one of the key pathological hallmarks of AD. Double immunihistochemical staining with tau and CoA antibodies in AD brain tissue revealed co-localisation of the two immunoreactive signals. Further, recombinant 2N3R and 2N4R tau isoforms were found to be CoAlated in vitro and the site of CoAlation mapped by mass spectrometry to conserved cysteine 322, located in the microtubule binding region. We also report the reversible H2O2-induced dimerisation of recombinant 2N3R, which is inhibited by CoAlation. Moreover, CoAlation of transiently expressed 2N4R tau was observed in diamide-treated HEK293/Pank1β cells. Taken together, this study demonstrates for the first time extensive anti-CoA immunoreactivity in AD brain samples, which occurs in structures resembling neurofibrillary tangles and neuropil threads. Covalent modification of recombinant tau at cysteine 322 suggests that CoAlation may play an important role in protecting redox-sensitive tau cysteine from irreversible overoxidation and may modulate its acetyltransferase activity and functional interactions.